Characterization of two insulin-binding components of rat-liver plasma membranes. Issue 10 (October 1982) - Baron, M. D.; Sónksen, P. H.
Abstract : We have identified and isolated two forms of insulin receptor from rat-liver plasma membranes. The smaller ( M r = 90k) is a single polypeptide. The same poly-peptide appears to be the insulin-binding site of the larger M r = 280k). Only the larger, multisubunit, receptor shows high-affinity binding of insulin and negative cooperativity in its dissociation kinetics.